The effect of high temperatures on seed germination of one native and two alien conifers in Patagonia - Boberg, Pelle (2010)
We examined the effect of thermal shock on the germination of seeds of three conifers, two introduced (Pseudotsuga menziesii and Pinus ponderosa), and one native to Patagonia (Araucaria araucana). Previous research has suggested increased susceptibility to invasions in burnt areas, and therefore, the effect of simulated fire (heat) on seed germination in these native and introduced species was compared. Seeds were heated to two different heat intensities (508C and 1008C) for 1 or 5 min, which is within the temperature range reached in the upper soil layers during forest fires. Germination tests were then carried out in a growth chamber. The heat treatments had a negative effect on the germination of P. menziesii at temperatures of 1008C, and a negative effect on the germination of P. ponderosa at the temperature of 1008C and the exposure of 5 min. The heat treatments had no affect at all on A. araucana. The species with larger seeds (A. araucana) had higher survival rates after the thermal shocks. Also intraspecific differences in seed sizes possibly point at larger seeds surviving thermal shocks better than smaller seeds. In addition, thermal shock caused a delay in the onset of germination in the two introduced species, while it did not change the time for germination in A. araucana.